Efektywność komunikowania a efektywność porozumiewania się - Domachowski, Waldemar (Człowiek i Społeczeństwo, 2020)
This article aims at describing the evidence for the efficacy of communication. The author differentiates effectiveness and efficacy of communication, as well as communication per se and communication with each other. He argues that there can be no discussion about the efficacy of communication without establishing its effectiveness. A communication process can be ineffective either when there is no recipient of the communicate or when the message is not received due to, for example, a noise. Even though the effectiveness can be measured using a nominal scale, the efficacy requires at least an ordinal scale. The author bases his conclusions on the theory of communication models, intentionality and, proposed by him, “a constant species”.